Stochastic Model Generation of Porous Rocks and Study on 2D Pore Morphology Influencing Rock Strength and Stiffness - Zhao, Lianheng; Deng, Min; Wang, Xiang; Huang, Dongliang; Zuo, Shi (Frontiers in Materials, 2022)
With the increasing usage of porous rocks in engineering construction, their well-performed properties (e.g., permeability and heat insulation) have attracted increasing attention from researchers in engineering geology. In nature, the vesicles in porous rocks always exhibit irregularity in morphology. This article proposes a workflow combining photogrammetry and Fourier transform to accurately acquire, characterize, and regenerate the natural pore morphology of porous rocks, including four steps: 1) initially, several 3D digital models of volcanic porous rock surfaces are reconstructed through a photogrammetry system, and the hollow pores in the surface are split into assemblies; 2) then, the 3D pore assembly is projected to a 2D reference plane with each pore being recognized and extracted; 3) the contours of a single pore are processed based on discrete Fourier transform (DFT), and a series of Fourier descriptors (mainly consist of D2, D3, and D8) are then statistically analyzed; 4) an inverse discrete Fourier transform (IDFT) is then conducted to quantitatively reconstruct the pores. Based on the earlier processes, the pores are distributed in a numerical model (rock failure and process analysis code, RFPA2D), and uniaxial compression simulations are performed to further investigate the influences of porosity and pore morphology on rock strength and stiffness. Herein, we introduce significant Fourier descriptors (i.e., D2, D3, and D8) as representations of three levels of pore morphology. Thus, 12 groups of numerical simulations considering the impact of porosity, pore orientation, D2, D3, and D8 are conducted. Results show that the porosity exerts a first-order control on the mechanical properties of rocks, while the effect of pore orientation is related to D2. All of them closely match those typically observed in previous studies. Furthermore, these simulations also highlight the influence of detailed pore morphology, such as convex hulls and subtle zigzags characterized by D3 and D8, respectively, on the rock failure process, marking that a more complicated morphology (e.g., with more convex hulls) may result in a reduction in rock strength and Young’s modulus. The proposed study provides a novel perspective on natural pore morphology together with its influence on rock strength and stiffness.